ESG disagreement and corporate debt maturity: evidence from China - Kangqi Jiang; Jie Zhang; Mengling Zhou; Zhongfei Chen (Financial Innovation)
Abstract This study explores the relationship between corporate environmental, social, and governance (ESG) disagreements and corporate debt maturity. By examining panel samples from Chinese non-financial listed companies covering 2007 to 2020, we find that ESG disagreements negatively influence corporate debt maturity. Even after conducting a series of robustness tests and addressing endogeneity concerns, the adverse effects of ESG disagreements persisted. A heterogeneity analysis shows that this negative impact is more significant for non-state-owned enterprises, small enterprises, enterprises with high capital intensity, enterprises with low analyst attention, and enterprises in high-tech industries. Through a mechanism analysis, we discovered that ESG disagreements can lead to information asymmetry and heightened default risk, subsequently affecting the maturity of corporate debt. Further analysis confirms that the negative impact of ESG on the debt structure inhibits long-term investment and exacerbates the mismatch between investment and financing terms.